1988
DOI: 10.1017/s0022112088001302
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent structure in low-concentration drag-reducing channel flows

Abstract: A two-component laser-Doppler velocimeter was used to measure simultaneously velocity components parallel and normal to the wall in two fully developed, wellmixed, low-concentration (1-2 p.p.m.) drag-reducing channel flows and one turbulent channel flow of water. The mean velocity profiles, root-mean-square velocity profiles and the distributions of the ūv turbulent correlation confirm that the additives modify the buffer region of the flow. The principal influence of the additives is to damp velocity fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
53
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 12 publications
17
53
0
Order By: Relevance
“…Donohue et al 22 examined the effects of polymers on turbulent structures by using the visualization technique; they reported that the streaking spacing and bursting rates in drag-reducing flow are different from that in the Newtonian flow, i.e., the average nondimensional spacing between streaks linearly increases with increasing DR and the viscous sublayer was more stable when polymer solutions were present. A suppression of the burst process and an increment of streak spacing were also reported by Berman 16 and Tiederman et al 23 However, Luchik and Tiederman 19 found that the method for deducing the time between bursts was not accurate in these experiments because they did not marked and counted all of these events. Thus, the flow visualization revealed some important phenomena, but a lack of measure of the corresponding turbulent velocity field limits the interpretation.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Donohue et al 22 examined the effects of polymers on turbulent structures by using the visualization technique; they reported that the streaking spacing and bursting rates in drag-reducing flow are different from that in the Newtonian flow, i.e., the average nondimensional spacing between streaks linearly increases with increasing DR and the viscous sublayer was more stable when polymer solutions were present. A suppression of the burst process and an increment of streak spacing were also reported by Berman 16 and Tiederman et al 23 However, Luchik and Tiederman 19 found that the method for deducing the time between bursts was not accurate in these experiments because they did not marked and counted all of these events. Thus, the flow visualization revealed some important phenomena, but a lack of measure of the corresponding turbulent velocity field limits the interpretation.…”
Section: Introductionsupporting
confidence: 63%
“…Two-component LDV measurements were conducted by many researchers. [17][18][19][20][21] All these experiments confirmed that the root mean square of the velocity fluctuations in the streamwise direction increases while the rms of the fluctuations in the wall-normal direction decreases with DR, and the Reynolds shear stress decreases in the drag-reducing flows. The sum of Reynolds shear stress and viscous shear stresses is lower than the total shear stress without the presence of polymer agents.…”
Section: Introductionsupporting
confidence: 55%
“…The theory gained support as experimental results gathered information on the normal rates of deformation encountered by the polymer solutions flowing close to walls, as in the boundarylayer studies of the bursting processes by Reischman and Tiederman [6] and Luchik and Tiederman [7], amongst others. According to these authors, the resistance of the fluid molecules to normal deformations increases enormously and non-linearly with the strain rates; this ever increasing resistance to normal deformation interferes with the turbulence production and especially with the turbulence dissipation mechanisms.…”
Section: Introductionmentioning
confidence: 85%
“…The phenomenon in the regions where drag reduction occurs with polymer additives were also discussed by Lumley [3] and Reischman and Tiederman [4] who presented experimental evidences that the buffer region changed and played an important role in drag-reducing flows. Measurements in chan-nel flow with polymer injection, using two-component laserDoppler velocimetry (LDV) were performed by Luchik and Tiederman [5] and Walker and Tiederman [6]. They reported that the addition of polymers caused a decrease in wall normal velocity fluctuations and a concomitant reduction of wall shear stress, which indicated a damping of energy exchange between near-wall region and outer region.…”
Section: Introductionmentioning
confidence: 99%
“…Luchik and Tiederman [5] employed mu-level method (modified ulevel method) on the coherent structures in turbulent channel flows for the LDV dataset to discuss the effects of polymers on the streak spacing, bursting frequency, and Reynolds stress. The mu-level method was employed by Luchik and Tiederman [13], and its detection function D(t) for the leading edge is defined by…”
Section: Introductionmentioning
confidence: 99%